RELIGIOUS DUALITY: PRE HINDU CULTURE EXISTENCE IN SELULUNG TRADITIONAL VILLAGE, KINTAMANI DISTRICT, BANGLI REGENCY - I Nyoman Dayuh; I Wayan Ardika; I Gede Sutarya; I Nyoman Subagia; I Gede Suwantana (UHN I Gusti Bagus Sugriwa Denpasar, 2022)
The hill of the Kintamani area with its misty natural conditions and cold nature makes it unique interms of religion and society, in contrast to the plains that are dominated by Hindu influence andclose to the aristocratic system. In the western part of Kintamani, there is Selulung Traditionalvillage which is still strong with a dualistic world view regarding its beliefs, socio-religions, andrituals. Belief in ancestors with the existence of Pura Kanginan-Kauhan, Palinggih Rong Kalih,Palinggih Dewa Hyang Kembar. A dualistic socio-religious system exists in the village eldercouncil called Ulu Apad which is divided into two, namely kiwa-tengen, sigar kanginan-sigarkauhan. Apart from that, there are also social rituals that are dualistic, such as the nyeheb rite, a riteasking for rain to the gods of the sky. This signifies a dualistic relationship between earth-heaven.